2018
DOI: 10.1021/acs.molpharmaceut.8b00246
|View full text |Cite
|
Sign up to set email alerts
|

BRCA Status Does Not Predict Synergism of a Carboplatin and Olaparib Combination in High-Grade Serous Ovarian Cancer Cell Lines

Abstract: Over 50% of epithelial ovarian cancers express the BRCAness profile that leads to a dysfunctional homologous recombination repair system. The combination of a dysfunctional homologous recombination repair system and a poly(ADP-ribose) polymerase (PARP) inhibitor results in a synthetic lethal phenotype. The PARP inhibitor olaparib, approved as a monotherapy for patients with a germline BRCA mutation, has shown promising results in preclinical studies when combined with DNA damaging agents, such as carboplatin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…PARPi is currently indicated as maintenance treatment for recurrent HGSOC following second line platinum-based therapy [39]. Previously, we reported that PARP1 protein levels were reduced following chemotherapy in vitro and in vivo [28].…”
Section: Discussionmentioning
confidence: 99%
“…PARPi is currently indicated as maintenance treatment for recurrent HGSOC following second line platinum-based therapy [39]. Previously, we reported that PARP1 protein levels were reduced following chemotherapy in vitro and in vivo [28].…”
Section: Discussionmentioning
confidence: 99%
“…Another notable example includes a study on the combination of carboplatin and olaparib conducted in high-grade serous ovarian cancer cells (HGSOC). [119] Synergy was observed in both BRCA1/2-proficient and -deficient cell lines, indicating that the therapeutic benefits of this combination is independent of BRCA status (Figure 8a). Mechanistic studies revealed that the synergy observed in BRCA-deficient UWB1.289 cell lines were due to increased DNA DSBs (Figure 8b).…”
Section: Combination Of Carboplatin and Olaparibmentioning
confidence: 99%
“…Western blotting and immunofluorescence studies indicated that this combination exerted its cytotoxicity via DNA damage, enhancing NHEJ repair while inhibiting HR repair. Another notable example includes a study on the combination of carboplatin and olaparib conducted in high‐grade serous ovarian cancer cells (HGSOC) [119] . Synergy was observed in both BRCA1/2‐proficient and ‐deficient cell lines, indicating that the therapeutic benefits of this combination is independent of BRCA status (Figure 8a).…”
Section: Parp Combination Therapy: a Promising Strategymentioning
confidence: 99%
“…Concomitant use of PARPi with a platinum agent has been tested in several types of cancer, demonstrating increased cytotoxicity [3135]. PARP inhibition potentiated platinum cytotoxicity in the O-342/DDP and CH1cisR platinum-resistant ovarian cancer cell lines [31, 32], as well as in the BRCA wt and BRCA 2-restored OV90 and PEO4 ovarian cancer cell lines, respectively [33]. The PARPi CEP-6800 and olaparib also enhanced platinum-induced cytotoxicity in HRR - proficient non-small cell lung and colorectal carcinomas, respectively [34, 35].…”
Section: Introductionmentioning
confidence: 99%